One new species of the genus Cyrtopsis (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China - Xu, Hao; Lv, Wenqing; Shi, Fuming (Zootaxa, 2025)
This paper reports one new species of the genus Cyrtopsis Bey-Bienko, 1962 from China, morphological photographs of the new species and Cyrtopsis robusta Liu & Zhang, 2007 collected from the type locality are provided.